Photovoice as a Method to Reduce the Stigma of Mental Illness Among Health Care Students. Issue 2 (March 2022) - Tippin, Gregory K.; Maranzan, K. Amanda
Photovoice is theorized to influence those who interact with the photos and captions, and so it is important to examine and further understand this mechanism. This article seeks to further our understanding of this critical process—that is, what is the impact of the Photovoice Artist's stories on the viewing audience? Herein we demonstrate how an incarnation of photovoice, digital storytelling, and photo elicitation impacted mental illness stigma among health sciences students. By focusing on application beyond the original exhibition, this article highlights how photovoice methods and aims overlap with best practices in stigma reduction, and its fit with multimodal anti-stigma interventions. Overall, this study contributes to addressing the question of how photovoice can be applied to achieve action for social change.